DIGITAL COMPETENCY SHIFTS AMONG EDUCATORS: DEVELOPMENTS, CHALLENGES AND OPPORTUNITIES - Devi Arhami Putri (Jurnal Ikhtibar Nusantara, 2026)
As the technological era has evolved, educational technology has transformed from the mere use of standalone devices into a key infrastructure for learning. This shift has also increased the demands placed on teachers’ digital competences. This narrative review synthesises 30 years of literature (1996–2026) to map the development of theoretical frameworks and institutional definitions regarding educators’ digital competences. This study traces the shift from operational skills in information and communication technology (ICT) towards pedagogical integration models such as TPACK and DigCompEdu, and on to a new paradigm focusing on generative artificial intelligence, data privacy, digital ethics and technology governance. The findings of the synthesis indicate that there remains a gap between teachers’ technical proficiency and their ability to integrate technology effectively into pedagogical practice. The latest literature also highlights a number of unresolved issues, namely the predominance of self-assessment-based surveys over performance-based assessments, the limited adaptation of digital competences to specific subjects and educational contexts, and the scarcity of research on developing education systems. Consequently, policies and professional development programmes need to shift from general software training towards standardised performance measurement, ethical AI governance, and competency frameworks tailored to specific needs and contexts. These findings offer a strategic roadmap for preparing educators to lead meaningful, effective and responsible digital learning amidst the evolution of AI-driven education.